مسألة اجتهاد النبي صلى الله عليه وسلم: إشكاليّة الفكرة والمصطلح: The Question of the Prophet’s Interpretive Reasoning: The Idea and the Concept Abstract - أبوسنينة عصام (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2016)
مسألة اجتهاد النبي ﷺهي من المسائل التي ألقت بظلالها على الفكر الإسلامي قديماً وحديثاً؛ لأنَّها تتعلَّق بإشكالية مهمة جداً هي إشكالية البشرية والوحي في حق النبي ﷺ يهدف هذا البحث إلى تفكيك هذه الإشكالية، وبناء صورة واضحة المعالم لتمييز تصرُّفات النبي ﷺ بصفته البشرية من تصرُّفاته التي أُوحي إليه فيها. ولهذا ناقش الباحث أقوال العلماء في هذه المسألة ليخرج بهذه الصورة التي تجمع بين النقل والعقل معاً. The issue of the interpretive reasoning (Ijtihad) of the Prophet، peace be upon him, is one that has casted its shadow on the ancient and contemporary Islamic thought. It is an issue of utmost importance، namely، the issues of the Prophet's humanness and Prophethood. This study aims to deconstruct this issue، and to build a well-defined understanding that distinguishes between the actions of the Prophet، peace be upon him، as a human being and his actions that are based on the Revelation in his capacity as a Prophet. The study discusses the positions of scholars on this issue to come the understanding that combines the revealed text and human reasoning.